Determinants and Challenges of Implementing One-Year Pre-Elementary Early Childhood Education Policy: A Case Study of Bintan Pesisir District, Indonesia - Zurmi Afriani; Rumzi Samin; Armauliza Septiawan (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to analyze the implementation of Regent Regulation Number 61 of 2019 concerning the Completion of One-Year Early Childhood Education Before Elementary School in Bintan Pesisir District, Bintan Regency. This research employed a descriptive qualitative approach using Merilee S. Grindle’s policy implementation theory focusing on content of policy and context of implementation. Data collection techniques included interviews, observations, documentation, and literature studies. Research informants consisted of the Bintan Regency Education Office, district government officials, PAUD managers, teachers, and community members. The results showed that the implementation of the policy had been carried out but had not run optimally. In terms of policy content, the policy has provided benefits in improving children’s readiness before entering elementary school, yet it still faces obstacles such as limited infrastructure, inadequate educators, and uneven distribution of PAUD institutions. Meanwhile, in the context of implementation, coordination among policy implementers has not been fully effective and public awareness regarding the importance of early childhood education remains low. Supporting factors include the existence of regional regulations, local government support, and the commitment of PAUD institutions. Inhibiting factors include limited resources, geographical conditions of coastal areas, and low community participation. This study recommends improving equal access to PAUD services, strengthening policy socialization, and enhancing the quality of educators and educational facilities in coastal areas of Bintan Regency.